Computational Screening of Anticancer Peptides from Cordyceps militaris Targeting Apoptosis, Angiogenesis, and Metastasis - Lim, Joanne; Chia, Adeline Yoke Yin; Chamyuang, Sunita; Quan, Tang Yin (UI Scholars Hub, 2025)
Cancer remains a major global health issue, and current therapies often lack efficacy and have severe adverse effects. Anticancer peptides (ACPs) have emerged as promising therapeutic agents due to their specific targeting mechanisms and minimal toxicity. This study aimed to identify novel ACPs from Cordyceps militaris through computational screening, evaluate their anticancer potential, predict their mechanisms of action through molecular docking, and analyze their pharmacokinetic profiles. Initially, 15 protein sequences from Cordyceps militaris were retrieved from the National Center for Biotechnology Information database and subjected to in silico gastrointestinal digestion using BIOPEP-UWM. The resulting peptides were subjected to predictive analysis via AntiCP2.0 and iACP-FSCM for their anticancer potential. The top 16 peptides were selected based on high prediction scores and subjected to molecular docking using HPEPDOCK and BIOVIA Discovery Studio against key cancer-related proteins, including anti-apoptotic Bcl-2 proteins (4B4S, 4AQ3), VEGFR2 kinase (3C7Q), and NF-κB (1SVC). The PATSW, SISVGW, and QCSEAGSSW peptides showed the strongest binding affinities, indicating potent anticancer activities. Pharmacokinetic prediction by ADMETlab 2.0 revealed favorable in vitro permeability but highlighted limitations in oral bioavailability, suggesting a requirement for further peptide modifications. Overall, this study identified promising candidates for anticancer therapeutics derived from C. militaris, supporting future experimental validations